Genesis characteristics and taxonomic classification of island hilly soils in Zhejiang Province - MA Wanzhu; ZHU Kangying; ZHUO Zhiqing; ZHANG Mingkui (浙江大学学报. 农业与生命科学版)
Islands have special geographical landscapes and complex soil forming conditions, where the soil formation is different from that in mainland areas. To understand the genesis characteristics and taxonomic classification of island hilly soils in Zhejiang Province, 80 soil profiles were surveyed combining with historical literature data in this study. The results showed that the geomorphic structures, parent materials, climatic conditions, and vegetation types of the soils were relatively single, but the soils were frequently affected by the island scales, distances from land, tide, and human activities. The terrain slope was large; the lithification was obvious; the clayization was weak; the desilicification-allitization was changeable; the weathering-leaching coefficient was medium; the restoring base cations were obvious; the pH value and base saturation percentage were higher than those in the mainland at the same latitude; and the soil forming environment was affected by both ancient and modern factors. Four soil orders, namely Ferrosols, Argosols, Cambosols, and Primosols, were identified from the islands of Zhejiang Province, including 7 suborders of Ustic Ferrosols, Udic Ferrosols, Ustic Argosols, Udic Argosols, Ustic Cambosols, Udic Cambosols, and Orthic Primosols, as well as 10 soil groups, 11 subgroups and 25 soil families. In conclusion, the direction of soil formation from the islands of Zhejiang Province is basically the same as that of mainland hilly soil at the same latitude, belonging to the traditional ‘red soil zone’.